Strengthening The Capacity of the Indonesian Ombudsman to Optimize Inclusive and Responsive International Cooperation - Pambudi, Andi Setyo (Departemen Ilmu Administrasi FISIP UNHAS, 2025)
Globalization and technological developments have expanded the scope of maladministration, which is no longer limited to domestic issues. Cross-border collaboration is becoming increasingly relevant to prevent and deal with mismanagement, especially in dealing with the complexity of problems in various fields. This requires a strategy that is effective nationally and capable of reaching a global dimension. Currently, the role of the Indonesian Ombudsman in the worldwide framework has not been utilized optimally. The involvement of the Indonesian Ombudsman in international collaborative efforts still faces various obstacles. Analyzing the potential and role of the Indonesian Ombudsman towards a strategic position for global cooperation is interesting to review as input for policymakers in the development context, which directly impacts public services, the economy, and society. This research aims to present a synthesis of the philosophy of establishing the Ombudsman, identify challenges that hinder the optimization of the Indonesian Ombudsman's contribution to cooperation, formulate strategies for strengthening capacity in its active role on a global scale, as well as provide policy considerations for strategic cooperation opportunities with international Ombudsman institutions or other global organizations to improve the quality of supervision of maladministration of public services. The analysis method used is qualitative through literature studies from various sources and Focus Group Discussions (FGD) in the PESTLE framework (Political, Economic, Social, Technological, Legal, and Environmental). By exploring strategic opportunities and discussing existing obstacles, it is hoped that this article can contribute to strengthening global governance of Ombudsman supervision that is more inclusive and responsive to the challenges of maladministration and providing comprehensive and integrated policy recommendations.